Single Stage Aortic Arch Replacement without Circulatory Arrest - Marenchino, Ricardo G; Domenech, Alberto (AORTA, 2016)
A 78-year-old man with a Kommerell diverticulum and aberrant right subclavian artery was admitted for thoracic pain and severe malnutrition due to esophageal compression. We performed an atypical surgical procedure including extra-anatomical debranching and direct aortic repair, trying to avoid deep hypothermic circulatory arrest and shorten the cardiopulmonary bypass time.
Keywords: Kommerell diverticulum; Arch aneurysm repair